Improving cervical cancer screening participation by introducing HPV vaginal self-sampling to women living with HIV in Denmark– a pilot study - Siri Nana Halling Svensgaard; Mette Tranberg; Berit Andersen; Lone Kjeld Petersen; Merete Storgaard; Sanne Jespersen (BMC Women's Health)
Abstract Background Cervical cancer, despite being largely preventable through vaccination and screening, continues to pose a significant global health challenge. Women living with HIV (WLWH) are at a six-fold higher risk of developing cervical cancer, primarily due to persistent infection with high-risk HPV (hrHPV). While effective screening methods have the potential to reduce this risk, WLWH remain inadequately screened. The aims of this pilot study were fourfold: To estimate the proportion of WLWH who are not screened according to WHO guidelines; to establish the proportion of WLWH who accepted the self-sampling offer; to estimate the hrHPV DNA prevalence; and to estimate the compliance to follow-up among women with a hrHPV-positive vaginal self-sample. Methods This single-centre, pilot study was conducted from February to May 2022 at the Department of Infectious Diseases, Aarhus University Hospital, Central Denmark Region. Eligible women were contacted by phone and invited to participate. Participants were provided with a self-sampling kit (Evalyn® Brush) and detailed instructions. The collected samples were analysed for hrHPV DNA using the COBAS® 4800 assay. Demographic, clinical, and screening history data were obtained from medical records and the Danish Pathology Databank. Results Of the 100 eligible participants, 50% (n = 50) accepted the offer of self-sampling, and 80% (n = 40/50) returned their samples for analysis. The prevalence of hrHPV among these women was 25% (n = 10/40). Follow-up compliance among hrHPV-positive women was 40% (n = 4/10). The analysis revealed that 41% (n = 41/100) of WLWH had not been screened in accordance with WHO guidelines, and 39% (n = 16/41) of the women had never undergone screening. No significant differences were observed in demographic or clinical characteristics between participants and non-participants. Conclusions Vaginal hrHPV self-sampling was acceptable and feasible for WLWH, with high return rates but suboptimal follow-up compliance. Enhancing participation and adherence is crucial for effective cervical cancer prevention. Larger studies are needed to validate these findings and optimize screening strategies. Trial registration The Central Denmark Region Committee on Health Research Ethics deemed this study as a quality improvement study on the 9th of November 2021 (request approval j.no: 204/1-10-72-274-21). Clinical trial number: Not applicable.